2018
DOI: 10.1002/anie.201711710
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Cysteine S‐Glycosylation Induced by Per‐O‐Acetylated Unnatural Monosaccharides during Metabolic Glycan Labeling

Abstract: The unexpected, non-enzymatic S-glycosylation of cysteine residues in various proteins by per-O-acetylated monosaccharides is described. This artificial S-glycosylation greatly compromises the specificity and validity of metabolic glycan labeling in living cells by per-O-acetylated azido and alkynyl sugars, which has been overlooked in the field for decades. It is demonstrated that the use of unacetylated unnatural sugars can avoid the artifact formation and a corrected list of O-GlcNAcylated proteins and O-Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 16 publications
(7 reference statements)
7
154
0
Order By: Relevance
“…Amazingly, using an Ac 4 ManNAz metabolic labeling strategy, sialylated N-glycans on a select group of small noncoding RNAs (glycoRNAs), including Y RNAs, have been observed in mammalian cells [140], which may update our knowledge towards biochemistry, as we already know [141]. It is worth noting that per-O-acetylated monosaccharides can spontaneously react with numerous cysteines in proteomes with non-enzymatic catalysis, resulting in abnormal S-glycosylation [142]. In consideration of this condition, it is necessary to verify the results by specific glycosylation sites to exclude the S-glycosylation on cysteines when performing sialoglycoprotein research using Ac 4 ManNAz.…”
Section: Sialic Acids Metabolic Glycan Labelingmentioning
confidence: 99%
“…Amazingly, using an Ac 4 ManNAz metabolic labeling strategy, sialylated N-glycans on a select group of small noncoding RNAs (glycoRNAs), including Y RNAs, have been observed in mammalian cells [140], which may update our knowledge towards biochemistry, as we already know [141]. It is worth noting that per-O-acetylated monosaccharides can spontaneously react with numerous cysteines in proteomes with non-enzymatic catalysis, resulting in abnormal S-glycosylation [142]. In consideration of this condition, it is necessary to verify the results by specific glycosylation sites to exclude the S-glycosylation on cysteines when performing sialoglycoprotein research using Ac 4 ManNAz.…”
Section: Sialic Acids Metabolic Glycan Labelingmentioning
confidence: 99%
“…The decoding of Sia code on G 1 with F‐ G 2 ‐Q (or Fuc code on G 3 with F′‐ G 4 ‐Q′) provides a hairpin opening‐derived fluorescence signal and releases P for the next catalytic cycle. A recent important finding of artificial cysteine glycosylation by the Chen group raises a caveat on the use of the metabolic engineering approach . In the case of MUC1, the three cysteines are located on the C‐terminal, intracellular region, and thus do not interfere with the extracellular HieCo imaging process.…”
Section: Methodsmentioning
confidence: 99%
“…Ar ecent study also reportedn onspecific reactions of cysteine residues with acetylated GalNAc/GlcNAc analoguest hat have been widely used for metabolic labeling of O-GlcNAci nc ells. [23] Finally, imaging can be difficult with proteins that are not highly glycosylated, and distance limitations between the fluorophores might restrict the application of FRET on certainlarge substrate proteins.O ther strategies such as SNAP-tag, which exploits an alkyltransferase (O 6 -alkylguanine-DNA-alkyltransferase) to label fusion proteins with af luorophore, could also be adapted to investigate OGT substratepreferences in cells. [84]…”
Section: Imaging Techniques To Investigate Ogtsubstrate-and Localizatmentioning
confidence: 99%
“…Moreover, differential O‐GlcNAcylation could result from an equilibrium of OGT and OGA activities. A recent study also reported nonspecific reactions of cysteine residues with acetylated GalNAc/GlcNAc analogues that have been widely used for metabolic labeling of O ‐GlcNAc in cells . Finally, imaging can be difficult with proteins that are not highly glycosylated, and distance limitations between the fluorophores might restrict the application of FRET on certain large substrate proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation